The Influence of Modified Hanging Ball Device on Volleyball Spike Performance in the Ngestiboga PWD Team - Rena Riskiana; Ginanjar Nugraheningsih (Pusdikra-Publishing.com, 2023)
This study aims to answer the following questions: (1) Does the hanging ball modification tool influence the results of volleyball smashes in the Ngestiboga PWD volleyball team? (2) To what extent does the hanging ball influence the results of volleyball smashes in the Ngestiboga PWD team? This research is a quantitative study using a one-group pretest-posttest design and quasi-experimental approach. Ten members of the Ngestiboga PWD volleyball team were used as the research sample. The sampling method employed was total sampling. The validity testing steps of the research instrument included testing the ability of volleyball smashes and using the Pearson product-moment correlation formula, which yielded an observed correlation coefficient (r) > the tabulated correlation coefficient (r-table) at 5%, namely 0.760 > 0.632, and a two-tailed Sig. value of 0.0011 < 0.05, indicating the accuracy of the data. The reliability test using Cronbach's alpha resulted in a high interpretation value of 0.805. Paired Sample T-test was used as the data analysis technique, along with homogeneity and homogeneity of variance tests as prerequisites for the Shapiro-Wilk normality test. The results of this study showed that the null hypothesis (Ho) was rejected, while the alternative hypothesis (Ha) was accepted (calculated t-value > tabulated t-value = 19.532 > 2.306). To draw conclusions, it is important to note that: (1) The hanging ball modification tool influences the results of volleyball smashes in the Ngestiboga PWD team. (2) The R Square value of 0.116 according to the linear regression test. The percentage of the impact of the Ngestiboga PWD team's reaction to the hanging ball modification on volleyball smash results is 11.6%, and 88.4% is influenced by other factors.